Epidemiological Aspects, Prenatal Screening and Diagnosis of Congenital Heart Defects in Beijing - Zhang, Yanchun; Zhang, Wen; Xu, Hongyan; Liu, Kaibo (Frontiers in Cardiovascular Medicine, 2021)
Background: In China, congenital heart disease (CHD) is the most common birth defect type, with approximately 13,000 new cases annually. This study aimed to investigate high-risk factors, prenatal screening and prenatal diagnosis as a basis for clinical decisions. Methods: All CHD cases identified from 2018–2020 were obtained from the Beijing city birth defect surveillance system and prenatal diagnosis institutions. The prenatal CHD diagnosis was confirmed by fetal echocardiography and amniotic fluid or cord blood genetic examination. Chi-square, odds ratio (OR), 95% confidence interval (CI), and univariate and multivariate logistic analyses were used to explore the high-risk factors, prenatal screening and prenatal diagnosis of CHD. Results: In total, 6,786/594,860 fetuses with CHD were diagnosed by prenatal echocardiography. The average incidence of CHD was 11.4 per1,000 births, with an increase of 30.7per 1,000 births from 2018–2020 (P<0.05); the average incidence of complex CHD (CCHD) was 2.02per 1,000 births, with no significant change from 2018–2020 (P>0.05). Women age ≥ 35 years (OR 1.06, 95% CI 0.77–1.46) was at higher risk of having babies with CHD than women aged 21–34 years. Overall, CHD incidence increased with maternal age (OR1.03, 95% CI 1.02–1.03). Additionally, women who had a nonlocal household registration (OR 1.16, 95% CI 1.10–1.22) or had diabetes mellitus (DM)(OR 1.16,95% CI 0.96–1.25) were at higher risk of CHD.As an independent factor, CCHD was related to maternal age, DM, fetal gender, and maternal education level (all p<0.05). The prenatal ultrasound screening detection rate of CCHD was 97.59%, which was far higher than that of total CHD (51.67%) (P<0.001). The prenatal ultrasound diagnosis rate of CCHD was higher than that of simple CHD (P<0.001), but the coincidence rate in the ultrasound diagnosis of CCHD was lower than that of simple CHD (P<0.001). Prenatal genetic testing revealed chromosomal abnormalities in 25.62% (279/1089) of CHD cases with indications for a prenatal diagnosis. Conclusions: Maternal age, household registration, multiple births and DM were related to CHD occurrence. Prenatal ultrasound screening is a highly effective method for CCHD diagnosis, and CHD fetuses should be closely evaluated to exclude chromosomal abnormalities.